2009
DOI: 10.1002/jso.21345
|View full text |Cite
|
Sign up to set email alerts
|

Technical feasibility and safety of laparoscopy‐assisted total gastrectomy in gastric cancer: A comparative study with laparoscopy‐assisted distal gastrectomy

Abstract: LATG is a technically feasible procedure as compared with LADG. However, its postoperative complication rate is higher than that of LADG, especially that of anastomotic stricture. A more effective anastomotic method during LATG is required to prevent stricture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
55
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 33 publications
5
55
0
3
Order By: Relevance
“…However, it has not become as popular as LADG because of its technical difficulty and because of concerns regarding postoperative complications [8,9]. Lee and colleagues [10] compared the surgical outcomes of LATG with those of LADG and found that the postoperative complication rate of LATG was higher than that of LADG, especially that of anastomotic stricture.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has not become as popular as LADG because of its technical difficulty and because of concerns regarding postoperative complications [8,9]. Lee and colleagues [10] compared the surgical outcomes of LATG with those of LADG and found that the postoperative complication rate of LATG was higher than that of LADG, especially that of anastomotic stricture.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the rate of anastomotic leakage was reported to be high, at 1.5% to 10.4%, after LATG, which is the current standard procedure used for tumors invading the upper stomach. 3,5 LAsTG was therefore considered to be a less hazardous surgery in terms of anastomotic leakage compared with LATG.…”
Section: Discussionmentioning
confidence: 99%
“…18 Conversely, the blood loss due to LATG was reported to be 182 to 190.7 mL. 3,9 Thus, LAsTG may slightly increase the risk of bleeding, especially around the spleen, compared with conventional LADG. However, the risk seems to be low compared with LATG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations